Effects of dietary leucine on growth, antioxidant capacity, immune response, and inflammation in juvenile yellow catfish Pelteobagrus fulvidraco - Feng, Dexiang; Yu, Yangping; Liu, Kaifang; Su, Yi; Fan, Tianyu; Guo, Xusheng; Li, Ming (Frontiers in Physiology, 2023)
The experiment was conducted to investigate the effects of dietary leucine on growth, antioxidant capacity, immune response and inflammation in juvenile yellow catfish. Five diets were formulated to contain five dietary leucine levels: 12.00 (control), 19.00, 26.00, 33.00 and 40.00 g kg -1. Each diet was randomly assigned to triplicate groups of 30 juvenile fish (5.02 ± 0.15 g) twice daily to apparent satiation for 56 days. Weight gain rate, specific growth rate, and activities of liver superoxide dismutase, glutathione peroxidase, and serum lysozyme, immunoglobulin M content significantly increased with dietary leucine level increased up to 26.00 g kg -1, but those values decreased significantly with a further increase in dietary leucine. On the contrary, the lowest malondialdehyde content was found in 26.00 and 33.00 g kg -1 leucine groups. The expression levels of IGF 1 and MYF 5 genes in muscle were significantly up-regulated with dietary leucine levels increased up to 26.00 g kg -1, but MSTN expression was the opposite. The lowest expression levels of IL 8 and TNFɑ genes in liver were found in 26.00 g kg -1 leucine groups. The quadratic regression analysis on weight gain, specific growth rate and feed conversion rate against dietary leucine levels indicated that the optimal dietary leucine requirement was estimated to be 26.84 – 27.00 g kg -1of the dry diet.